Digital History Konzepte, Methoden und Kritiken Digitaler Geschichtswissenschaft - Döring, Karoline Dominika; Haas, Stefan; König, Mareike; Wettlaufer, Jörg (Studies in Digital History and Hermeneutics, 2022)
Research and teaching in history have undergone profound changes within the scope of digitalization. This volume asks questions such as: What changes is digitalization making possible in the way that historical research is carried out and communicated today? What new objects, methods, and tools are available to researchers today and what research findings do they produce?